Overlapping the Right to Education and Justice: Discursive Configuration - Mercedes Ruiz Muñoz (Universidad Autónoma de Madrid, 2015)
The present paper is the result of on going research in the area of justice and the right to education which aims to provide an account both of the significations constructed by the various agents involved and of political stances in this area. We focus here on elements of meaning encoded in the discourse configuration relating to the right to education and its interdependency with justice. Our theoretical and methodological perspective falls within a political analysis of educational discourse, with the notion of discourse configuration serving as an analytical device. We are particularly interested in identifying, through the analysis of documents and interviews, discourse traces relating to justice and the right to education. Among our results, while we do find that elements of discourse configuration in relation to the right to education-such as whether it is cost-free, mandatory, legislable and an enforceable right as well as other frequently-discussed elements relating to justice, such as fairness and equality-are clearly argued and documented, in the present work we aim to contribute to the discussion on justice and the right to education by showing them to be interrelated concepts.